The Grassland–Shrubland Regime Shift in the Southwestern United States: Misconceptions and Their Implications for Management. (3rd September 2018) - Bestelmeyer, Brandon T; Peters, Debra P C; Archer, Steven R; Browning, Dawn M; Okin, Gregory S; Schooley, Robert L; Webb, Nicholas P
Abstract: Transitions from semiarid grassland to shrubland states are among the most widely recognized examples of regime shifts in terrestrial ecosystems. Nonetheless, the processes causing grassland–shrubland transitions and their consequences are incompletely understood. We challenge several misconceptions about these transitions in desert grasslands, including that (a) they are currently controlled by local livestock grazing and drought events, (b) they represent severe land degradation, and (c) restoration of grassland states is impossible. Grassland–shrubland transitions are the products of multiple drivers and feedback systems, both ecological and social, interacting at multiple scales of space and time. Grass recovery within shrubland states—with and without shrub removal—produces novel ecosystems that are dissimilar from historical grasslands but that provide important ecosystem services. Projected increases in climate variability are likely to promote the further displacement of perennial grasses by xerophytic shrubs. This article offers guidelines for managing grassland–shrubland transitions in the face of changing biophysical and socioeconomic circumstances.